Acceleration of start-up of moving bed biofilm reactor at low temperature by adding specialized quorum sensing bacteria. (August 2022) - Fu, Hui-min; Wang, Jinfeng; Ren, Hongqiang; Ding, Lili
Graphical abstract: Highlights: Bioaugmented MBBR achieved higher COD and NH4 + -N removal rate. Bioaugmented BH3 T increased the adhesion properties of the biofilm. Bioaugmented BH3 T promoted the growth of functional bacteria at low temperatures. Bioaugmented BH3 T promoted the rapid start-up of the reactor at low temperatures. Abstract: This study aims to accelerate biofilm formation and operational performance of moving bed biofilm reactor (MBBR) at 5 ℃ by adding specialized Quorum Sensing bacteria ( sphingomonas rubra BH3 T ). Results showed that bio augmented MBBR (RS ) achieved a higher chemical oxygen demand and NH4 + -N removal rate (93% and 75%), which in accordance with its increased biofilm thickness, higher biofilm activity, and nitrifying bacteria abundance ( Nitrospira ). The increased biofilm thickness (60.23 %) during the whole operating time, accompanied by more potent adhesion force (61.59 %), was related to increased polysaccharides and proteins in the biofilm. Pyrosequencing analysis indicated that BH3 T contributed to higher species richness and triggered the rapid growth of precursor microorganisms ( Nakamurella, Micropruina, and Zoogloea ) and the enrichment of multifunctional microorganisms ( Pseudomonas, Aeromonas, Arcobacter, Dechloromonas, and Flavobacterium ) at low temperatures. This study provides an economical and practical new insight into accelerating start-up of MBBR system at low temperature.